(untitled) (Nordic Journal of African Studies, 2001)
This paper addresses the problem of language as a tool in the expression of an African form of Christianity. In particular, it describes how a Nigerian religious community, Ijo Orile Ede Adulawo Ti Kristi (National Church of Christ), founded in 1919 by the Reverend Adeniran Ake in Ibadan, established its place later in Ile-Ife State under the protection of the traditional leadership. Through this example the paper argues that the indigenisation of an African Christian religion can be attained through the use of a local language, a local culture with its beliefs and practices, and adherence to the biblical roots of Christianity. Although the movement has been agitated to cut ties with the mainstream Christianity, it has not done so. The fact that it also maintains several schools, at least some with good reputation, shows that it has extended its influence also to the educational sector. This church has also motivated other indigenous Churches in the Yoruba-speaking area in Nigeria to try to integrate the biblical foundations with African heritage in an authentic manner. (Ed.)